Comparison of modified concept pr 100 and spray-dried animal plasma on nursery pig performance - Wiedmann, E.J.; DeRouchey, Joel M.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (My University, 2009)
One hundred eighty weanling pigs (initially 11.3 lb and 18 ± 2 d of age) were used in a 28-d growth assay to determine if Modified Concept PR 100 (MCNPR), a plant-based protein ingredient containing added synthetic amino acids and nucleic acids, can replace spray-dried animal plasma (SDAP) in nursery pig diets. The five experimental treatments were: 1) control (no specialty protein source); 2) 2.5% SDAP; 3) 5.0% SDAP; 4) 2.5% MCNPR; and 5) 5.0% MCNPR. Treatment diets were fed from d 0 to 14 post-weaning, with a common diet fed to all pigs from d 14 to 28 post-weaning. Analyzed values of MCNPR were noticeably lower than the manufacturer provided values used in diet formulation. The difference in calculated and analyzed lysine values would decrease the total dietary lysine content by 0.027 and 0.056% for the 2.5 and 5.0% MCNPR, respectively. From d 0 to 14, pigs fed increasing SDAP had improved (linear, P<0.01) ADG, ADFI, and F/G, which was primarily due to a large improvement from the 0 to 2.5% SDAP inclusion, with further increases when 5.0% was fed. In addition pigs fed increasing levels of MCNPR had improved (quadratic, P<0.002) feed efficiency, with pigs fed 2.5% MCNPR having the maximum response. While no statistical differences (P>0.21) were detected in ADG and ADFI for pigs fed increasing levels of MCNPR, there were improvements by approximately 21 and 11%, respectively, over the control diet. However, pigs fed SDAP had greater (P<0.05) ADG, ADFI, and BW at d 14 compared to pigs fed MCNPR. Overall (d 0 to 28), pigs fed increasing SDAP from d 0 to 14 had greater (P<0.03) ADG and tended to have improved (P<0.08) ADFI and F/G. Also, pigs fed increasing MCNPR had improved (quadratic, P<0.01) feed efficiency, with pigs fed 2.5% MCNPR having the maximum response. While no statistical differences (P>0.18) were detected in ADG and ADFI for pigs previously fed increasing MCNPR, there were improvements by approximately 10 and 7%, respectively, over the control diet. Although the magnitude of difference between pigs fed SDAP and MCNPR was maintained to the end of the trial, there were no overall significant differences in growth between pigs fed SDAP and MCNPR (P>0.21). These results indicated that SDAP and MCNPR can effectively be used in nursery pig diets to improve growth performance when used as a partial replacement for soybean meal. However, pigs fed SDAP had greater performance than pigs fed MCNPR during the test period, but these differences were not found at the conclusion of the studies.
Keywords: Feed ingredients; Modified concept PR 100; Spray-dried animal plasma; Swine